Structure and superconductivity of isotope-enriched boron-doped diamond - Ekimov, Evgeny A (Sci Technol Adv Mater, 2009)
Superconducting boron-doped diamond samples were synthesized with isotopes of (10)B, (11)B, (13)C and (12)C. We claim the presence of a carbon isotope effect on the superconducting transition temperature, which supports the ‘diamond-carbon’-related nature of superconductivity and the importance of the electron–phonon interaction as the mechanism of superconductivity in diamond. Isotope substitution permits us to relate almost all bands in the Raman spectra of heavily boron-doped diamond to the vibrations of carbon atoms. The 500 cm(−1) Raman band shifts with either carbon or boron isotope substitution and may be associated with vibrations of paired or clustered boron. The absence of a superconducting transition (down to 1.6 K) in diamonds synthesized in the Co–C–B system at 1900 K correlates with the small boron concentration deduced from lattice parameters.